Recent discoveries on the acquisition of the highest levels of human performance - Güllich, A.; Barth, M.; Hambrick, D. Z.; Macnamara, B. N. (Science, 2025)
Structured Abstract BACKGROUND Exceptional performers push the boundaries of human capability, drive innovation, and help solve the world`s most pressing problems. For decades, research on the acquisition of human performance across domains (e.g., science, academia, music, sports, and chess) has primarily been conducted with young and sub-elite performers. This research suggested that, within these populations, higher early performance and larger amounts of discipline-specific practice generally are predictors of better later performance. Correspondingly, many elite schools, universities, conservatories, and youth sport academies around the world typically aim to select the top-performing young people and then seek to further accelerate their performance through intensified discipline-specific practice. Given that previous expertise research largely focused on young performers and that many elite training programs aim to select the top-performing young people, two critical questions arise: (i) Are exceptional performers at young ages and at later peak performance age largely the same individuals? And (ii) do predictors of young exceptional performance also predict later exceptional peak performance? Until recently, these questions were not systematically investigated among the world`s best performers across domains. ADVANCES In recent years, research on the acquisition of exceptional performance has progressed. Several large datasets from adult world-class performers have become available to review and synthesize. The present literature review synthesizes findings on the development of more than 34,000 adult international top performers in different domains, including Nobel laureates, the most renowned classical music composers, Olympic champions, and the world`s best chess players. The available evidence suggests a common pattern across domains with three major features. (i) Early exceptional performers and later exceptional performers within a domain are rarely the same individuals but are largely discrete populations over time. For example, world top-10 youth chess players and later world top-10 adult chess players are nearly 90% different individuals across time. Top secondary students and later top university students are also nearly 90% different people. Likewise, international-level youth athletes and later international-level adult athletes are nearly 90% different individuals. (ii) Most top achievers (Nobel laureates and world-class musicians, athletes, and chess players) demonstrated lower performance than many peers during their early years. Across the highest adult performance levels, peak performance is negatively correlated with early performance. (iii) The pattern of predictors that distinguishes among the highest levels of adult performance is different from the pattern of predictors of early performance. Higher early performance in a domain is associated with larger amounts of discipline-specific practice, smaller amounts of multidisciplinary practice, and faster early discipline-specific performance progress. By contrast, across high levels of adult performance, world-class performance in a domain is associated with smaller amounts of discipline-specific practice, larger amounts of early multidisciplinary practice, and more gradual early discipline-specific performance progress. These predictor effects are closely correlated with one another, suggesting a robust pattern. OUTLOOK The new evidence enhances our understanding of how world-class performance develops. The similar developmental pattern of world-class performers across different domains suggests widespread, if not universal, principles underlying the acquisition of exceptional human performance. Assumptions suggested by the evidence from young and sub-elite performers, along with other approaches discussed in the literature, cannot adequately explain the recent evidence. New explanations may further advance scientific understanding. As a starting point, we suggest three explanatory hypotheses: the search-and-match hypothesis, the enhanced-learning-capital hypothesis, and the limited-risks hypothesis. On the basis of the recent evidence, scientists can enhance theories, program managers can promote evidence-based practices, and policy-makers can better allocate funding. Such efforts may foster opportunities to enhance world-class performance across science, sports, music, and other fields.